PENGARUH UMUR DAN POSIS! DALAM POHON TERHADAP BEBERAPA SIFAT FISIS KAYU - Suparman Karnasudirdja; Edi Sarwono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Pinus merkusii or locally known as Tusam, is one of the plantation species extensively cultiuated in the uarious part of Indonesia. The uses of its wood uary from chopstick and ice cream spoon to some construction item such as trans- mission pole, and a possible use of its wood for cooling tower is still being studied.The paper describes study result of the effect of tree age and position within tree on some physical properties (Specific grauity, moisture content, uolumetric shrinkage and fiber saturation point). The results were computed using the nested or hierarchical classification analysis, and the differences between means tested using Tukey's w procedure.The results shows that the tree age effect significantly the green and air-dry specific gravity, The other properties do not seem to be affected. Between tree differences affect significantly the air-dry moisture content only. Height within tree does affect uery significantly the uolumetric shrinkage from green to ouen dry condition; and from air-dry to ouen dry condition. The ouerall mean and standard deviation ualues for each property had been calculated and the result presented.